Congenital Cytomegalovirus and Hepatic Failure: An Underrecognized Complication. Issue 2 (21st October 2021) - Souder, J. Paige; Grimm, Erica; Pinninti, Swetha; Boppana, Suresh; Hsu, Evelyn; Horslen, Simon; Pacheco, M. Cristina; Kunz, Anjali; Sainato, Rebecca
Abstract : Congenital cytomegalovirus infection is the most common congenital infection. Although most infants with congenital cytomegalovirus infection are asymptomatic at birth, a subset will have readily apparent clinical and/or laboratory manifestations including hepatitis; progression to hepatic failure has not previously been described in term infants who initiated antiviral treatment shortly after birth. We present 2 term infants with congenital cytomegalovirus infection and hepatitis who progressed to hepatic failure despite initial laboratory improvement on therapy.